Design of Immersion Electrostatic LensOperated under Zero Magnification Condition (Baghdad Science Journal, 2025)
The inverse problem is important method in the design of electrostatic lenses which is used in this work, with new technique by suggesting an axial electrostatic potential distribution using polynomial functions of the third order. The paraxial-ray equation is solved to obtain the trajectory of particles that satisfy the suggested potential function.In this work design of immersion electrostatic lens operated under zero magnification condition. The electrode shape of sthe electrostatic lens was the dermined from the solution of laplace equation and plotted in two deimensions . The results showed low values of spherical and chromatic aberrations , which are considered as good criteria for good desigh.